Discovery and Optimization of Tau Targeted Protein Degraders Enabled by Patient Induced Pluripotent Stem Cells-Derived Neuronal Models of Tauopathy - Silva, M. Catarina; Nandi, Ghata; Donovan, Katherine A.; Cai, Quan; Berry, Bethany C.; Nowak, Radoslaw P.; Fischer, Eric S.; Gray, Nathanael S.; Ferguson, Fleur M.; Haggarty, Stephen J. (Frontiers in Cellular Neuroscience, 2022)
Accumulation of misfolded, aggregating proteins concurrent with disease onset and progression is a hallmark of neurodegenerative disorders known collectively as proteinopathies. An important class of these are tauopathies, such as frontotemporal dementia (FTD) and Alzheimer’s disease (AD), associated with the accumulation of aberrant forms of tau protein in the brain. Pathological tau undergoes abnormal post-translational modifications, misfolding, oligomerization and changes in solubility, cellular redistribution, and spreading. Modeling these pathological tau conformers ex vivo remains a challenge due to context-dependent neuronal expression of tau isoforms and of modifying enzymes, and the physiological differences of commonly used immortalized neuronal cell lines. In this study, we employed FTD-patient induced pluripotent stem cells (iPSC)-derived neurons, expressing a tau variant or mutation, as primary models for driving a medicinal chemistry campaign. We describe structure-activity relationships (SAR) around a series of direct tau targeting degraders culminating in the identification of QC-01-175 and follow-up optimization strategies for the lead molecule. Overall, these studies demonstrate the further potential for targeted protein degradation in the context of central nervous system proteinopathies and beyond.